Nanangenines: drimane sesquiterpenoids as the dominant metabolite cohort of a novel Australian fungus, Aspergillus nanangensis - Heather J. Lacey; Cameron L. M. Gilchrist; Andrew Crombie; John A. Kalaitzis; Daniel Vuong; Peter J. Rutledge; Peter Turner; John I. Pitt; Ernest Lacey; Yit-Heng Chooi; Andrew M. Piggott (Beilstein Journal of Organic Chemistry, 2019)
Chemical investigation of an undescribed Australian fungus, Aspergillus nanangensis, led to the identification of the nanangenines – a family of seven new and three previously reported drimane sesquiterpenoids. The structures of the nanangenines were elucidated by detailed spectroscopic analysis supported by single crystal X-ray diffraction studies. The compounds were assayed for in vitro activity against bacteria, fungi, mammalian cells and plants. Bioinformatics analysis, including comparative analysis with other acyl drimenol-producing Aspergilli, led to the identification of a putative nanangenine biosynthetic gene cluster that corresponds to the proposed biosynthetic pathway for nanangenines.